Luminescent metal-organic frameworks (MOFs) as a chemopalette: Tuning the thermochromic behavior of dual-emissive phosphorescence by adjusting the supramolecular microenvironments - Zhan, Shun-Ze; Li, Mian; Ng, Seik Weng; Li, Dan (Wiley, 2013)
Two classical copper(I)-cluster-based luminophores, namely, Cu 4I4 and [Cu3Pz3]2 (Pz=pyrazolate), are immobilized in a supramolecular system through the formation of metal-organic framework (MOF) materials. This series of luminescent MOF materials, namely, [Cu4I4(NH3)Cu 3(L1)3]n, [Cu4I4(NH 2CH3)Cu3(L1)3]n, and [Cu4I4Cu3(L2)3]n (L1=3-(4-pyridyl)-5-(p-tolyl)pyrazolate; L2=3-(4-pyridyl)-5-(2,4-dimethylphenyl) pyrazolate), exhibit diverse thermochromism attributed to the relative functioning efficacy of the two coordination luminophores. Such an intriguing chemopalette effect is regulated by the different supramolecular microenvironments between the two-dimensional layers of these MOFs, and in particular, by the fine-tuned Cu-Cu distances in the excimeric [Cu 3Pz3]2 luminophore. The structure-property elucidation of the thermochromic behavior allows one to understand these optical materials with unusual dual-emissive properties. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.